Arsenic adsorption by Bacterial Extracellular Polymeric Substances - Ahsan, Nazmul; Faruque, Kashfia; Shamma, Farah; Islam, Nazrul; Akhand, Anwarul A (Bangladesh Journal of Microbiology, 2012)
The main objective of this work was to isolate arsenic resistant bacteria from contaminated soil, followed by screening for their ability to adsorb arsenic. Six bacterial isolates (S1 to S6) were obtained from arsenic contaminated soil samples and among these, five (S1, S2, S3, S5 and S6) were characterized as bacillus and the rest one (S4) was cocci depending on shape. All the isolates except S6 produced extracellular polymeric substances (EPS) in the culture medium and displayed arsenic adsorbing activities demonstrated by adsorption of around 90% from initial concentration of 1 mg/L sodium arsenite. To clarify the role of EPS, we killed the bacteria that produced EPS and used these killed bacteria to see whether they could still adsorb arsenic or not. We found that they could adsorb arsenic similarly like that of EPS produced live bacterial isolates. From the observation it is concluded that these isolates showed potentiality to adsorb arsenic and hence might be used for bioremediation of arsenic. DOI: http://dx.doi.org/10.3329/bjm.v28i2.11821 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 80-83